SERUM β2 MICROGLOBULIN AND LACTATE DEHYDROGENASE 2 ISOENZYME AS MARKERS OF BONE MARROW INFILTRATION IN NON-HODGKIN LYMPHOMA: Markers of Bone Marrow Infiltration in Non-Hodgkin Lymphoma - Mazher, Naghmana; Ahmed, Nisar; Iqbal, Zafar (Pakistan Armed Forces Medical Journal, 2017)
Objective: To determine the levels of serum lactate dehydrogenase 2 (LD2) Isoenzyme and β2 microglobulin (β2m) in patients of non-Hodgkin’s lymphoma (NHL) and to correlate these levels in NHL patients with and without bone marrow infiltration.Study Design: Cross sectional study.Place and Duration of Study: Post Graduate Medical Institute, Lahore and Centre of Excellence in Molecular Biology (CEMB), Lahore, from 2008 to 2010.Material and Methods: The study was conducted on 80 subjects irrespective of age and sex and divided into three groups i.e. group A comprising 20 normal healthy controls, group B 30 patients of NHL without bone marrow infiltration while group C consisted of 30 NHL patients with bone marrow infiltration. Serum β2m and LD2 isoenzyme levels were determined in the subjects and the values were compared with healthy age and sex matched controls. The estimations were made prior to the institution of chemotherapy.Results: Serum β2 microglobulin and LD2 levels were significantly raised in NHL patients compared with controls. There was also significant difference when the values were compared between the patients of NHL with and without bone marrow infiltration.Conclusion: The levels of β2m and LD2 showed positive correlation with the extent of the disease, so we conclude that non-invasive parameters are useful indicator of the extent of the disease.